النظام القانوني لموظفي أسلاك الأمن الوطني في التشريع الجزائري - خماس, عبد الله; جديدي, ضياء الدين; منانة, عبد الحكيم (My University, 2023)
هدفت هذه الدراسة إلى تحديد الأحكام والضوابط التي تحكم المسار الوظيفي لموظف الأمن الوطني، من خلال تمييزه عن بقية الموظفين، والعلاقة التي تربطه بالإدارة، والشروط الموضوعية والإجرائية للالتحاق بالأمن الوطني. الخدمة، من تعيين وتدرج، ثم ترسيم، مما يكسبه صفة الموظف ويجعله محاطا بالحماية. وتعترف له الدولة بالحقوق والضمانات المميزة وتلزمه بأداء واجباته وأوضاعه القانونية ووسائل النقل والضمانات التأديبية التي شرعها له القانون حتى انتهاء علاقته الوظيفية، إما نهاية عادية أو نهاية غير عادية.This study aimed to determine the provisions and regulations that govern the career path of the national security employee, by distinguishing him from the rest of the employees, the relationship that binds him to the administration, and the objective and procedural conditions for joining the national security service, from appointment and internship, followed by demarcation, which earns him the status of an employee and makes him surrounded by protection. The state recognizes privileged rights and guarantees for him and obliges him to perform his duties, legal statuses, transportation and disciplinary guarantees that the law has legislated for him until the termination of his functional relationship, either an ordinary end or an extraordinary end.
مذكرة ماستر
Keywords: : موظف عمومي- الأمن الوطني-المسار المهني-الترسيم _الضمانات التأديبية; public employee - national security - professional path - registration - disciplinary guarantees